„Jak żyć po czymś takim w Polsce?” Edukacyjne walory podróży na przykładzie Dziennika podróży do Italii i Szwajcarii z lat 1815–1816 Rozalii Dunin-Borkowskiej - Sijka, Katarzyna (Biuletyn Historii Wychowania, 2020)
A Diary of a Journey to Italy and Switzerland in 1815–1816 written by Rozalia Dunin-Borkowska is one of few preserved descriptions of a journey to Italy made by a Polish woman in the early 19th century. Rozalia and her husband Stanisław embarked on their expedition on 27 May 1815 in Lvov; they went to Italy and spent nine months there, from October 1815 to July 1816. The Italian tour started in Venice and included Padua, Bologna, Florence (twice), Rome, Naples, Milan and Geneva. The spouses spent the journey actively although their main goal was to learn about the culture of the Italian Peninsula. Undoubtedly, their time in Italy was filled with admiring the works of art and visiting the most famous art galleries in almost every city on the itinerary. Consequently, the journal is full of reflections on the aesthetic value of Italian works of art. Rozalia Dunin-Borkowska was an informed traveller: while she admired the sights and paintings, sculptures and other works of art, she did that in a thoughtful way. She needed quality time to form her own opinions. Her journal demonstrates very well that visiting foreign countries was an intellectually stimulating experience. Getting to know a new culture significantly broadened the horizons of 24-year-old Rozalia. As her journal suggests, she was well-prepared for her European journey. The outstanding lesson that she learnt allowed her to reap the rewards of the tour and satisfy her intellectual aspirations. The Diary is a great source of experience accumulated by a Polish traveller; it provides an opportunity to find out about Rozalia’s cultural life, her preparation for the journey and how the trip affected her. Furthermore, Dunin-Borkowska’s testimony was compared with Katarzyna Platerowa’s and Teofilia Morawska’s diaries due to the fact that all three of them shared certain common features. Namely, their cultural background, material status and, most importantly, the travel itinerary. They were all well prepared for their respective journeys; they were also well educated, fluent in foreign languages and, above all, they were curious about the world and interested in learning about a new culture. Each of these travellers was influenced by the European journey which provided educational values combined with unforgettable experiences.